Profile of Ethical Complaints against Doctors in One a Brazilian State, from 2001 to 2016 (Revista Iberoamericana de Bioética, 2022)
Over the last few decades, medicine has suffered due to an increasing number of ethical complaints and legal procedures. This paper evaluated the reports assessed by the Piauí State Regional Medical Council from 2001 to 2016. 1011 investigations were included and 1073 doctors were involved. There was a significant increase in the number of physicians reported over time (p
Keywords: ethics; medical; bioethics; medical errors; defensive medicine